Predictors of autosomal dominant polycystic kidney disease progression: a Brazilian single-center cohort - Nishimoto, Igor Hitoshi [UNESP]; Santos, Andrey Gonçalves [UNESP]; Bianchini, Júlia Mandelbaun [UNESP]; Santos, Luiz Gustavo Brenneisen [UNESP]; Martini, Maria Carolina Rodrigues [UNESP]; dos Santos Silva, Vanessa [UNESP]; Martin, Luis Cuadrado [UNESP] (FapUNIFESP (SciELO), 2024)
Introduction: Identifying risk factors for autosomal dominant polycystic kidney disease (ADPKD) progression is important. However, studies that have evaluated this subject using a Brazilian sample is sparce. Therefore, the aim of this study was to identify risk factors for renal outcomes and death in a Brazilian cohort of ADPKD patients. Methods: Patients had the first medical appointment between January 2002 and December 2014, and were followed up until December 2019. Associations between clinical and laboratory variables with the primary outcome (sustained decrease of at least 57% in the eGFR from baseline, need for dialysis or renal transplantation) and the secondary outcome (death from any cause) were analyzed using a multiple Cox regression model. Among 80 ADPKD patients, those under 18 years, with glomerular filtration rate <30 mL/ min/1.73 m2, and/or those with missing data were excluded. There were 70 patients followed. Results: The factors independently associated with the renal outcomes were total kidney length – adjusted Hazard Ratio (HR) with a 95% confidence interval (95% CI): 1.137 (1.057–1.224), glomerular filtration rate – HR (95% CI): 0.970 (0.949–0.992), and serum uric acid level – HR (95% CI): 1.643 (1.118–2.415). Diabetes mellitus - HR (95% CI): 8.115 (1.985–33.180) and glomerular filtration rate – HR (95% CI): 0.957 (0.919–0.997) were associated with the secondary outcome. Conclusions: These findings corroborate the hypothesis that total kidney length, glomerular filtration rate and serum uric acid level may be important prognostic predictors of ADPKD in a Brazilian cohort, which could help to select patients who require closer follow up.
Preditores de progressão da doença renal policística autossômica dominante: uma coorte brasileira de centro único
Keywords: Mortality; Polycystic Kidney, Autosomal Dominant; Rate; Renal Insufficiency; Risk Factors